Systematic review of invention education research landscape: state of the discipline and future directions - Dalela, Suhani; Ahmed, Muhammad S. (Frontiers in Education, 2024)
Invention and innovation education and its associated practices (e.g., problem-finding, problem-defining, learning from failure, iterative problem-solving, innovation-focused curricula, collaboration, and maker spaces) are moving from the periphery to the center of education at an ever-increasing pace. Although the research and literature on invention and innovation education, collectively termed as Invention Education (IvE) in this research, is on the rise, to our knowledge no attempt has been made to systematically review the literature available on the topic. To address this gap, we identify, collect, and systematically review scientific literature on IvE. We conduct Bibliometrix-based and targeted analysis to identify the topics, sources, authors, and articles most cited, as well as prominent countries publishing IvE literature. Another objective of this research is to uncover the intellectual, conceptual, and social structures of IvE. A third objective is to identify the progress made and the challenges being faced in furthering IvE and propose future directions. Our review shows that the field has seen substantial growth, especially in recent years particularly in the USA. Research shows IvE’s importance in nurturing a well-rounded, innovative, and skilled future workforce, emphasizing creativity, critical thinking, collaboration, adaptability, and problem-solving skills. Although with a plethora of curricula and K-20 programs in USA, followed by South Korea, and China, IvE lacks unifying conceptualization, definitions and frameworks. The lack of commonly accepted terms and theoretical bases, and difficulties integrating invention into STEM coursework, are compounded by barriers like resource limitations, curriculum constraints, and the need for teacher training and support. The review underscores the need for IvE to address and dismantle inventor stereotypes and cultivate a diverse and inclusive generation of innovators. It points to the impact of gender and stereotypes on participation in IvE programs and the importance of promoting equity and access to IvE opportunities for all students. The article concludes with a discussion of challenges and future research directions to address them.